Dinamika Komunitas Samin Perspekif Sejarah Studi Kasus Di Kudus Jawa Tengah - Rosyid, Moh. (Lambung Mangkurat University, 2023)
This paper explanation the dynamics of life Samin community in Kudus Central Java. Data collected by observation, interview, and references was analyzed using a qualitative descriptive. Result, Samin is Javanese ethnic community the originally driven by Ki Samin Surosentiko against invaders in Blora, Central Java. Its existence extends to city Kudus until now. Samin in Kudus face the dynamics of life the result (1) Saminisme the teachings passed down by oral history and nobody’s controlling, (2) life style following dynamics in this era. The impact change a down quality and quantity.